2015
DOI: 10.1002/cphc.201500439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Substitution in V2O3 on the Metal–Insulator Transition

Abstract: The effect of N-doping on the paramagnetic-antiferromagnetic transition associated with the metal-insulator (M-I) transition of V O at 150 K has been studied in bulk samples as well as in nanosheets. The magnetic transition temperature of V O is lowered to ∼120 K in the N-doped samples. Electrical resistivity data also indicate a similar lowering of the M-I transition temperature. First-principles DFT calculations reveal that anionic (N) substitution and the accompanying oxygen vacancies reduce the energy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For example, N substitution in V 2 O 3 decreases the IMT transition temperature. [ 13 ] Recently, Chouteau et al [ 14 ] have also demonstrated that N doping into VO 2 can cause the insulator monoclinic‐to‐metallic tetragonal phase transition, with a decreased T c from 68 °C to 50 °C. Important realization include chemical doping may activate or enhance the dimerization linked to the shortening of interatomic distances.…”
Section: Introductionmentioning
confidence: 99%
“…For example, N substitution in V 2 O 3 decreases the IMT transition temperature. [ 13 ] Recently, Chouteau et al [ 14 ] have also demonstrated that N doping into VO 2 can cause the insulator monoclinic‐to‐metallic tetragonal phase transition, with a decreased T c from 68 °C to 50 °C. Important realization include chemical doping may activate or enhance the dimerization linked to the shortening of interatomic distances.…”
Section: Introductionmentioning
confidence: 99%